СПЕЛЕОТЕРАПІЯ ЯК ВИСОКОЕФЕКТИВНИЙ МЕТОД ЛІКУВАННЯ ДІТЕЙ, ЯКІ ХВОРІЮТЬ НА БРОНХІАЛЬНУ АСТМУ, У МІЖНАПАДОВИЙ ПЕРІОД - Симулик, В. Д.; Золіна, О. В.; Туряниця, С. М.; Білак, В. М. (Проблеми клінічної педіатрії, 2021)
Abstract. The aim of the study was to study the effectiveness of speleotherapy and justify the feasibility of repeated courses of treatment according to clinical and follow-up indicators using indicators of non-specific resistance of the organism. Materials and methods: 179 children with bronchial asthma underwent clique-laboratory examination in the dynamics of speleotherapy treatment. Special studies of the enzymatic activity of neutrophilic granulocytes in peripheral blood were performed by cytochemical methods in 115 children. The activity of alkaline phosphatase (AL) was determined by the azo combination method according to MG Shubich (1965), myeloperoxidase (MP) -benzidine method (VA Almazov and SI Ryabov, 1963). The results of cytochemical reactions were evaluated according to the principle of L. Kaplow (1955), with the subsequent derivation of the average cytochemical coefficient (SCC). Along with this, the indicators of total activity (CAE) of MP and LF in one liter of blood were determined (MI Lazoryk, 1988). The functional activity of neutrophilic granulocytes in the blood of sick children was characterized by indicators of phagocytosis activity which were determined in 52 sick children according to the method of EF Chernushenko and LS Kogosova (1978) using a test microbe (staphylococcal strain № 9). Cytomorphological studies of sputum were performed in 53 children by immersion microscopy of stained sputum preparations. Evaluation of the results of cytological examination was performed according to the method of Gamarota (1974), and bacterioscopic determination of the microflora - according to the method of VI Svetovidova (1973). The results of follow-up studies revealed an extension of the period of stable remission (from 7 months to a year or more) in children who underwent repeated courses of treatment from 44% to 87%. It should be noted that in the remote period after the course of speleotherapy the course of exacerbation of the disease was characterized by a shorter duration and easier course. Studies of the morphofunctional properties of neutrophilic granulocytes in the peripheral blood of children with asthma have shown that complex treatment using repeated courses of speleotherapy led to the normalization of leukocyte formulations and normalization of parameters and activity parameters. Cytomorphological studies of sputum of children with asthma who underwent one and two courses of speleotherapy showed that regardless of the frequency of treatment, the inflammatory process of the bronchial mucosa remained, which requires further continuation of complex treatment. Under the influence of speleotherapy, a decrease in the processes of desquamation of the epithelium of the mucous membrane of the deep parts of the bronchi and a decrease in the intensity of the predominantly allergic component of the inflammatory reaction were observed. Conclusions. Сlinical and laboratory study of children with asthma treated by speleotherapy indicates its high efficiency, especially when repeated courses, as evidenced by the partial normalization of the resistant function of blood granulocytes and the elimination of local manifestations of inflammatory response of the bronchial mucosa.